Plantations Under the Famine Relief Scheme Bahraich Forest Division - Nautiyal, B. (Indian Forester, 1953)
This note describes the work done in respect of raising plantations of several valuable miscellaneous species of commercial importance in Bhinga and Charda blocks over a total area of 760 acres during 1952 under the Famine Relief Scheme. By giving employment to several thousand famine stricken villagers the scheme afforded them great relief. It briefly comments on the selection of suitable areas, method of soil working, plantation technique adopted, choice of species, method of sowing, nature of fencing and subsequent tending including weeding and protection and also establishing nurseries at several places. A statement showing the details of the expenditure on each item is appended.